The perfect molecule for hormonal contraception: Estetrol benefits. A review - Elena A. Gorbunova; Inna A. Apolikhina (Гинекология)
The article addresses studies of estetrol (E4) use as part of combined oral contraceptives (COCs) and its various effects on the body. Despite the rapid recovery of fertility after discontinuation of COCs, their popularity is declining due to adverse side effects such as weight gain, mood changes, poor menstrual control, and mastalgia. Therefore, the potential of the natural fetal estrogen E4, with high bioavailability and low risk of metabolic sequelae, is being studied. The data analyzed suggest that E4 may reduce the risk of breast cancer, as it induces less breast cell proliferation compared to other estrogens. During E4 therapy, the risk of venous thromboembolism is minimized, and there is less impact on hepatic enzymes, which improves the quality of sexual life and opens up the opportunities of prescribing COCs with E4 to women who are continuously receiving other drugs – statins, antiretroviral agents, or anticonvulsants. The article highlights promising results from clinical studies that confirm the efficacy of E4-based COCs, showing high levels of patient satisfaction. Clinical use of COCs with E4 can improve quality of life by eliminating the adverse effects associated with sexual function and providing high control over the menstrual cycle. Further research is needed on the impact of COCs with E4 on the psycho-emotional state and quality of women's sexual life, as well as the possible therapeutic effects of E4-based COCs, which will individualize the approach to contraception and provide women with safer and more effective options.